From competition to a sustainable raw materials diplomacy : pointers for European policymakers - Müller, Melanie; Saulich, Christina; Schöneich, Svenja; Schulze, Meike (2023)
Zusammenfassung: German and European businesses are highly dependent on metals. Demand for these raw materials is expected to grow even further as they will be needed for the green energy and electric mobility transition, digitalisation and other emerging technologies. Geopolitical developments influence security of supply. China’s central role in mineral supply chains is a major factor of uncertainty in this context. The European Union has set ambitious sustainability targets. Implementing these in complex multi-tier metal supply chains is no easy matter, given the magnitude of environmental and human rights risks. Nevertheless, sustainability should not be sacrificed for security of supply. Instead, the European Union should pursue a strategic raw materials policy that reconciles the demands of both. The two biggest challenges in sustainability governance are: firstly, the diversity of standards and their inconsistent implementation and enforcement; and secondly, power asymmetries and lack of transparency along metal supply chains. A sustainable raw materials policy must seek to reduce dependency through strategic diversification and partnerships with countries that share European values. Transparency-enhancing measures and a regulatory "smart mix"will be decisive elements